Indirect Effect of Azithromycin Use on the Intestinal Microbiome Diversity of Untreated Children: A Randomized Trial. (6th February 2019) - Oldenburg, Catherine E; Sié, Ali; Coulibaly, Boubacar; Ouermi, Lucienne; Dah, Clarisse; Tapsoba, Charlemagne; Bärnighausen, Till; Lebas, Elodie; Arzika, Ahmed M; Cummings, Susie; Zhong, Lina; Lietman, Thomas M; et al.
Abstract: Cohabiting children may share components of their intestinal microbiome. We evaluated whether receipt of azithromycin in one sibling confers changes to the intestinal microbiome in an untreated sibling compared with placebo in a randomized controlled trial. We found no evidence of an indirect effect of antibiotic use in cohabiting children. Clinical Trials Registrations: NCT03187834.